2012
DOI: 10.1148/radiol.12111873
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis: Detecting Changes in Airway Inflammation with FDG PET/CT

Abstract: FDG PET/CT is a useful tool for detecting inflammatory changes resulting from treatment for pulmonary exacerbations in pediatric patients with CF. Inflammatory changes detected by using FDG PET/CT correlated with lung function, sputum neutrophil counts, and CF-CT scores. Analyzing focal lung inflammation (with SUV(max)) may be a feasible way to measure airway inflammation in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
0
29
0
1
Order By: Relevance
“…Previous computed tomography studies have demonstrated that all of these factors can improve with treatment of a pulmonary exacerbation, but that the predominant component may vary between patients [12,13]. Recent studies would suggest that mucus plugging, and specifically large-airway mucus plugging changes more than other aspects of CF lung disease with antibiotic therapy [12,41]. In contrast, LCI is affected by heterogeneities at all levels of the airway tree, including peripheral airway disease, and changes in bronchomotor tone do not affect the measurement as much as FEV1, as demonstrated by studying LCI before and after administration of bronchodilators [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous computed tomography studies have demonstrated that all of these factors can improve with treatment of a pulmonary exacerbation, but that the predominant component may vary between patients [12,13]. Recent studies would suggest that mucus plugging, and specifically large-airway mucus plugging changes more than other aspects of CF lung disease with antibiotic therapy [12,41]. In contrast, LCI is affected by heterogeneities at all levels of the airway tree, including peripheral airway disease, and changes in bronchomotor tone do not affect the measurement as much as FEV1, as demonstrated by studying LCI before and after administration of bronchodilators [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Normalizing it for the air fraction will likely improve its accuracy as a reflection of lung cell metabolic activity (38). Normalization for blood (such as the tissue-toblood ratio, as explored in a dog model of ARDS (46)) may further improve the accuracy of V B ; however, whether this approach is comparable to correcting for V B as measured by kinetic analysis or other imaging (such as 15 O-CO scans) remains to be seen.…”
Section: Analysis Methods and Their Applications In Lung Diseases Quamentioning
confidence: 99%
“…Inflammation characterizes several lung diseases, including pneumonia, cystic fibrosis, chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome (ARDS), asthma, and interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF), among others (7,8,10,11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Because ARDS, COPD, and IPF can cause significant variability in the amounts of air, blood, and water in the lungs (Fig.…”
Section: Clinical Applications Investigated With 18 F-fdg Pet Imagingmentioning
confidence: 99%
“…Also, the combination of CT and PET scan in fusion images using fluorodeoxyglucose (FD) PET/CT is a useful tool for detecting inflammatory changes resulting from treatment for pulmonary exacerbations in pediatric patients with CF. These changes correlated with lung function, sputum neutrophil counts, and CF-CT scores, quantified by using standardized uptake values (SUVs) [12].…”
Section: Outcomes In Trials For Rare Pulmonary Diseasesmentioning
confidence: 99%